Bull field fertility differences can be estimated with in vitro sperm capacitation and flow cytometry - Zoca, Saulo Menegatti; Geary, Thomas W.; Zezeski, Abigail L.; Kerns, Karl C.; Dalton, Joseph C.; Harstine, Bo R.; Utt, Matthew D.; Cushman, Robert A.; Walker, Julie A.; Perry, George A. (Frontiers in Animal Science, 2023)
This study evaluated whether post in vitro capacitation changes in sperm could be used to estimate fertility differences between bulls. Frozen-thawed semen from five bulls (two to four ejaculates per bull) previously identified as high (48.1% and 47.7%), intermediary (45.5%) or low (40.7% and 43.1%) fertility, based on pregnancy per AI (P/AI), were evaluated for total and progressive motility, sperm plasma membrane integrity (viability), acrosome integrity (viable sperm with an intact or disrupted acrosome), reactive oxygen species (ROS; viable sperm ROS+ or ROS-), mitochondrial membrane energy potential, zinc signatures (signatures 1-to-4) and CD9 protein populations at pre-wash and post-wash (only total and progressive motility), h0 (diluted with non-capacitation media), and at h0, 3, 6, and 24 after dilution with capacitation media (CM) and incubation at 37ºC. Data were analyzed using the GLIMMIX procedure as repeated measures in SAS with bull, time and the interaction as fixed effects. Bull by time interaction was significant (P≤0.03) for total motility, viability, viable sperm with disrupted acrosome, and zinc signature 3. There tended (P=0.06) to be a bull by time interaction for zinc signatures 1+2 combined. Time was significant (P≤0.003) in all analyses, except viable ROS- (P=0.12). There was a significant effect of bull (P≤ 0.03) for viability, viable sperm with disrupted acrosome, zinc signatures 1, 2 and 1+2, viable CD9- and dead CD9+. High and intermediary fertility bulls had greater (P≤0.04) percentages of viable sperm, zinc signature 2 and zinc signature 1+2 compared to low fertility bulls. High and intermediary fertility bulls had decreased (P≤0.05) percentage of dead CD9+ compared to low fertility bulls. Viable CD9+ differed (P=0.02) and viable sperm with an intact acrosome and viable CD9+ tended to differ (P=0.06) amongst bulls; however, association with field fertility was not observed. There was a positive correlation between P/AI and zinc signature 2 (P=0.04), and there tended to be a positive correlation between P/AI and viability (P=0.10), and zinc signature 1+2 (P=0.10). In summary, incubation of sperm in CM and flow cytometry analyses for viability, zinc signatures 2 and 1+2, and dead CD9+ seems promising to estimate in vivo fertility differences amongst bulls.